RELIGIUSITAS, NORMA SUBJEKTIF DAN KONTROL PERILAKU DIPERSEPSIKAN TERHADAP KEPATUHAN WAJIB PAJAK KOTA PATI TAHUN 2020 - Estiningtyastuti Estiningtyastuti; Nuradi Karhananto (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine how much influence religiosity, subjective norms and perceptions of behavioral control have on individual taxpayer compliance. This study uses quantitative methods, namely by presenting research results in the form of numbers which are then explained and interpreted in a description, in order to test hypotheses. The subjects of this research are taxpayers who register their business with the Cooperatives and SMEs Service in Pati Regency. The data used in this study is primary data obtained from respondents who filled out the questionnaire. The sample in this study were 150 responden business taxpayers in Pati Regency who were registered in 2020 as many as 8472 SMEs. Results statistic explained that religious attitudes affect taxpayer compliance, subjective norms and behavioral control have no effect on SMEs taxpayer compliance in Pati Regency. Subsequent research in order to be able to conduct research again in the future by adding other research variables that can affect taxpayer compliance. For example, adding taxpayer knowledge variables, fines, trust in the government and others.